PENGARUH KECENDERUNGAN PEMILIHAN RISIKO DALAM PENGAMBILAN KEPUTUSAN INVESTASI YANG DIMODERASI OLEH GENDER: PENDEKATAN EKSPERIMEN - Dheni Indra Kusuma; Daniel Joel Immanuel Kairupan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to conduct laboratory experiments to examine the tendency of risk selection as a variable that affects managers in making investment decisions. Gender factor is used as a moderating variable in this study. Gender differences are thought to play a role as a variable that strengthens or weakens managers in making investment decisions. Research data collection was carried out using a 1 x 2 experimental design between subjects. Experiments will be carried out using a computer assisted program. Regarding the Covid-19 pandemic, the experiment will be carried out online with the help of zoom technology and google form with a limited time so that it approaches the experiment which is carried out directly through face to face. Hypotheses were tested using Pearson Chi Square statistical tools and ANOVA Two Way with Interaction. The result of this research is the tendency of risk selection affects investment decision making. while gender is not a moderating variable in this study.